Umno must face challenges positively, say analysts - The Edge, Financial Daily (The Edge, 2016)
KUALA LUMPUR: Since the inception of Umno on May 11, 1946, the party has grown from strength to strength, progressing with maturity as seen in the way the party has dealt with various challenges that have come its way.